Functional Gastrointestinal Disorders in under 4 years population specimen in Pakistan - Cheema, Sehrish Mukhtar; Hasan, Shamama; Ikram, Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pakistan is 6th most populous country in the world with an enormous pediatric population. No study has ever been conducted in Pakistan using the Rome IV criteria. The current study aimed to fill the gap. Methods: A cross-sectional survey of 59 attendants in a tertiary care hospital in Pakistan, using the Rome IV criteria. Results: Infant colic was the commonest FGID under nine months old while constipation was more common from six months to 18 months Conclusions: Infantile colic was the most common FGID in this small survey, but larger studies are needed.